Drying Characteristics of Papaya (Carica Papaya L.) Fruit Leather Using Microwave Oven - Purbasari, Dian; Wicaksono, Vicky Andhik; Taruna, Iwan; Yosika, Nur Ida Winni (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Fruit leather is a thin sheet of oven-dried fruit flesh. While papaya fruit is a perishable fruit with various types of fruit leather is one of the processed food products that can be preserved and has added value. This study aimed to determine papaya fruit leather’s drying characteristics using a microwave oven, namely changes in water content, drying rate, color, and water activity. The methods used were experimental methods with treatment variables of different microwave power (329 W, 428 W, and 701 W) and material thickness (1 mm, 3 mm, and 5 mm). The research design was selected in complete randomization with 3 replications. The results showed that the moisture content value decreased from 87.10-87.67%bb to 10.21-16.51%bb. The highest drying rate occurred at 701 W power and 1 mm material thickness with a value of 282.79%bb. The highest total color (∆E) value occurred in the treatment of 701 W power and 1 mm material thickness which was 28.78. The highest water activity (aw) value occurred at 329 W power treatment and 5 mm material thickness which was 0.463. Keywords: Drying, Fruit leather, Microwave, Papaya.